GENE-11. SHARED LONG NON-CODING RNA DYSREGULATION IN HISTONE H3 K27M GLIOMAS AND PF-A EPENDYMOMAS. (23rd April 2019) - Sanders, Lauren; Cheney, Allison; Field, Andrew; Beale, Holly; Kephart, Ellen; Learned, Katrina; Bjork, Isabel; Durbin, Ann; Lyle, Geoff; Pfeil, Jacob; Salama, Sofie; Haussler, David; et al.
Abstract: Diffuse pediatric gliomas harboring a Histone H3 K27M mutation are significantly more aggressive than H3-wild type gliomas and demonstrate global hypomethylation at the K27 residue 1 . As a result, these tumors show global aberrant gene expression, resulting in a primitive, stem-like proliferative cell population 2 . Posterior fossa (PF) ependymomas, on the other hand, harbor few significantly recurrent somatic mutations, but PF-A and PF-B subgroups have been defined on the basis of epigenetic differences 3 . Compared to PF-B, the PF-A subgroup demonstrates H3K27 hypomethylation, aberrant gene expression and aggressive tumor growth 4, 5 . We recently identified a set of long non-coding RNA (lncRNA) that are transiently expressed in early brain development 6, and hypothesized that H3K27M gliomas and PF-A ependymomas may share methylation-related dysregulation of long non-coding RNA (lncRNA) networks responsible for maintaining normal differentiation programs. Here we describe a network of regulatory lncRNA with increased expression in both H3K27M gliomas and PF-A ependymomas, as compared to H3-WT gliomas and PF-B ependymomas. We demonstrate that increased expression of this lncRNA network correlates with the over-expression of signaling pathways involved in maintaining a non-differentiated, proliferative phenotype and driving tumorigenesis. We hypothesize that in both H3K27M gliomas and PF-A ependymomas, aberrant global methylation may be driving lncRNA to activate and maintain stem-like states in early neural development, suggesting similarities in epigenetically driven, developmental origins for both tumor types. References: 1. Chan KM, Fang D, Gan H, et al. Genes Dev. 2013;27(9):985–90; 2. Filbin MG, Tirosh I, Hovestadt V, et al. Science. 2018;360(6386):331–5; 3. Witt H, Mack SC, Ryzhova M, et al. Cancer cell. 2011;20(2):143–57; 4. Bayliss J, Mukherjee P, Lu C, et al. Sci. Transl. Med. 2016;8(366):366ra161; 5. Mack SC, Witt H, Piro RM, et al. Nature. 2014;506(7489):445; 6. Field AR, Jacobs FM, Fiddes IT, et al. bioRxiv. 2017:232553.